(untitled) (Fiep Bulletin - online, 2014)
Corporal activities coming from the expression, communication joy and freedom are importants elements to the Educational System. In face of it in the year of 2005 in the Elementary School was created this project named: “Net in Dance”. To search a pedagogical practice through the dance, makes possible to the students, become this corporal language transforming and not reproducing.